Anthroponymy of Crimean Italians: Identity Dynamics Through Lens of History - E. D. Ivanova (Научный диалог)
This article explores the anthroponymy of descendants of Italian settlers in Crimea and its connection to the cultural and ethnic identity of Italians, which has evolved over the 20th and 21st centuries. The aim of this study is to provide a comprehensive understanding of the peculiarities of anthroponymy among Crimean Italians from a historical perspective, particularly concerning naming practices and name changes. The research draws on data from sociolinguistic interviews conducted with members of the Italian community in 2024. The analysis is framed within an emic approach. It is shown that in the early 20th century, names of Italian origin predominated within the community, whereas during the 1940s, due to deportation and a partial renunciation of identity, the use of Italian names sharply declined. Currently, there is a resurgence of interest in Italian names, indicating a growing connection to national roots. The study concludes that the choice of ethnically marked names is linked to the process of returning to Italian cultural identity. The novelty of this research lies in its introduction of data on the list of proper names (personal names) and the dynamics of their usage within the Italian community of Crimea into scholarly discourse.